2013
DOI: 10.4028/www.scientific.net/amr.721.603
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Herbal Compound Beverage of <i>Radix </i><i>astragali </i>on Immunosuppressed Mice Induced by Cyclophosphamide

Abstract: In this study, the herbal compound beverage of Radix astragali (HCBRA) was explored and the immuno-enhancement effects of HCBRA were studied in immunosuppressed mice induced by cyclophosphamide (Cy). HCBRA consisted of a water extract of the mixed herbal drugs Radix astragali, Golden-silk jujube, Acanthopanax senticosus fruit, Schisandra chinensis, Glycyrrhiza, Ginger, Peppermint. Compound polysaccharide content calculated as glucose equivalents was 120mg glucose/100mL beverage. The BALB/c mice were gavaged (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…After oral administration of AR polysaccharides in cyclophosphamide-induced rat, spleen weight, peripheral white blood cell counts, and T cell and B cell proliferation responses were significantly upregulated [ 45 ]. Furthermore, splenic nature killer cell activity and peritoneal macrophage phagocytosis were also dramatically increased [ 45 ].…”
Section: The Pharmaceutical Value Of Ar Extract and Ar Major Ingrementioning
confidence: 99%
See 1 more Smart Citation
“…After oral administration of AR polysaccharides in cyclophosphamide-induced rat, spleen weight, peripheral white blood cell counts, and T cell and B cell proliferation responses were significantly upregulated [ 45 ]. Furthermore, splenic nature killer cell activity and peritoneal macrophage phagocytosis were also dramatically increased [ 45 ].…”
Section: The Pharmaceutical Value Of Ar Extract and Ar Major Ingrementioning
confidence: 99%
“…After oral administration of AR polysaccharides in cyclophosphamide-induced rat, spleen weight, peripheral white blood cell counts, and T cell and B cell proliferation responses were significantly upregulated [ 45 ]. Furthermore, splenic nature killer cell activity and peritoneal macrophage phagocytosis were also dramatically increased [ 45 ]. In humans, the intake of AR extract promoted immunomodulating effects by upregulating the proliferation of peripheral blood mononuclear cells, as well as inducing interleukin production [ 46 ].…”
Section: The Pharmaceutical Value Of Ar Extract and Ar Major Ingrementioning
confidence: 99%
“…Modern pharmacological researches showed that it had significant cardiovascular system protection, anti-inflammatory, antitumor, antioxidant and improved immunity effects (Meng et al, 2021;Wei et al, 2021;Wang et al, 2022;Chen et al, 2023;Yang et al, 2023). As a homology between medicine and food product, Astragalus membranaceus plays an important role in dietary supplements due to its diverse chemical composition and pharmacological action and is mainly applied in the production of functional beverages, cookies, yogurt, etc (Lim et al, 2013;Liu et al, 2013). Lim et al developed rice wine cake cookies with different ratio of Astragalus membranaceus.…”
Section: Introductionmentioning
confidence: 99%